Analisis Strategi Kepala Sekolah dalam Mengatasi Kendala Supervisi Klinis di SD Insan Amanah Kota Malang - Hayyina Hayyina Zulfatul Layli; Dany Muhammad Dany Rohman; Ainni Nur Ainni; Hardianto Hardianto; Shobi Shobiyatul Fithroh Noviyanti (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
This study aims to analyze the principal’s strategies in overcoming the challenges of clinical supervision implementation at SD Insan Amanah Malang City. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects consisted of the principal as the main informant, as well as teachers and students as supporting informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was tested using source and technique triangulation. The findings revealed that the implementation of clinical supervision encountered several obstacles, including the principal’s limited time due to structural responsibilities, the dynamic classroom conditions of students, and differences in teachers’ pedagogical readiness. To address these challenges, the principal implemented strategies such as delegating supervision tasks to senior teachers, optimizing subject-group forums as professional learning communities, applying gradual coaching based on teachers’ needs, and utilizing students’ perceptions as supporting evaluation data. These strategies proved effective in fostering a culture of professional reflection, enhancing collaboration among teachers, and improving teachers’ pedagogical competence and the quality of learning in a sustainable manner.